Hubungan Jumlah Leukosit Darah Dan Pemeriksaan Mikroskopis Feses Terhadap Penyebab Infeksi Pada Penderita Diare Akut Usia 2–5 Tahun Yang Dirawat Di Rsud Ahmad Yani Kota Metro - M. Haikal; Tri Umiana Soleha; Rika Lisiswanti (Medula, 2020)
Diarrhea is the discharge of stool with a watery form and with more frequencies than usual. Diarrhea is a leading cause of death in children in developing countries with an interpretation of 1.3 billion events and 3.2 million deaths of toddler each year. Diagnosis of diarrhea is required, including complete blood count examination, serum electrolyte, urea and creatinine levels, faecal examination, and Enzym-linked immunosorbent assay (ELISA) giardiasis and serological test of amebiasis, and x-ray images of the abdomen. Stool examination and examination of blood leukocyte counts are closely related to the etiology of diarrheal diseases. The design of this study is comparative analytic with cross sectional approach to 16 DM patients and 16 subjects with impaired glucose tolerance (IGT). The data taken is primary data in the form of blood test result. The variables of this study are DM patients and subjects with IGT and the platelet indices (MPV and PDW-CV) of the two groups. A total of 19 respondents with elevated blood leukocytes with microscopic examination of bacterial/parasitic faeces were 17 respondents or 47% and with non bacterial/parasitic infections there were 2 respondents or 6%. Of the 17 respondents who did not increase blood leukocyte level there were 4 respondents or 11% with bacterial/parasitic infection and 13 respondents or 36% with infectious causes other than bacteria/parasite. Chi-square test results obtained ρ value = 0.00 ≤ α = 0.05. There is correlation between blood leukocyte count of microscopic examination of faeces in patients with acute diarrhea age 2-5 years.